2011
DOI: 10.1503/jpn.100041
|View full text |Cite
|
Sign up to set email alerts
|

Complementary diffusion tensor imaging study of the corpus callosum in patients with first-episode and chronic schizophrenia

Abstract: Background: Abnormalities in the corpus callosum have long been implicated in schizophrenia. Previous diffusion tensor imaging (DTI) studies in patients with different durations of schizophrenia yielded inconsistent results. By comparing patients with different durations of schizo phrenia, we investigated if white matter abnormalities of the corpus callosum emerge at an early stage in the illness or result from pathological progression. Methods: We recruited patients with first-episode schizophrenia, patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 46 publications
3
52
1
1
Order By: Relevance
“…Diffusion-weighted imaging has been relatively consistent in reporting reduced callosal FA in chronic schizophrenia (Douaud et al, 2007;Koch et al, 2010;Kubicki et al, 2008;Miyata et al, 2010;Mori et al, 2007b;RotarskaJagiela et al, 2008), including during remission (Koch et al, 2010) and less consistently in studies examining individuals at the first episode (Cheung et al, 2008;Gasparotti et al, 2009;Perez-Iglesias et al, 2010b;Peters et al, 2008;Price et al, 2005;Szeszko et al, 2005) or in earlier stages of illness (Davenport et al, 2010;Douaud et al, 2007;Kyriakopoulos and Frangou, 2009). Directly comparing first episode and chronic groups supports more severe changes in FA in the genu of the corpus callosum (Friedman et al, 2008;Kong et al, 2011), the left ILF (Friedman et al, 2008), and ALIC (Bora et al, 2011) in the chronic group including relative to the first episode group. By contrast, the large scale metaanalysis by Bora et al (2011) has reported the opposite, specifically for the genu of the corpus callosum, with FA being lower in the first episode relative to the chronic group with schizophrenia.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Diffusion-weighted imaging has been relatively consistent in reporting reduced callosal FA in chronic schizophrenia (Douaud et al, 2007;Koch et al, 2010;Kubicki et al, 2008;Miyata et al, 2010;Mori et al, 2007b;RotarskaJagiela et al, 2008), including during remission (Koch et al, 2010) and less consistently in studies examining individuals at the first episode (Cheung et al, 2008;Gasparotti et al, 2009;Perez-Iglesias et al, 2010b;Peters et al, 2008;Price et al, 2005;Szeszko et al, 2005) or in earlier stages of illness (Davenport et al, 2010;Douaud et al, 2007;Kyriakopoulos and Frangou, 2009). Directly comparing first episode and chronic groups supports more severe changes in FA in the genu of the corpus callosum (Friedman et al, 2008;Kong et al, 2011), the left ILF (Friedman et al, 2008), and ALIC (Bora et al, 2011) in the chronic group including relative to the first episode group. By contrast, the large scale metaanalysis by Bora et al (2011) has reported the opposite, specifically for the genu of the corpus callosum, with FA being lower in the first episode relative to the chronic group with schizophrenia.…”
Section: Discussionmentioning
confidence: 95%
“…In WM, a single study of individuals experiencing their first psychotic episode did not detect microstructural changes (as assessed by DTI) in the corpus callosum relative to healthy controls (Price et al, 2005). Studies including both first episode and chronic patients showed that patients with chronic disease had significantly reduced FA compared with controls, reaching only a trend level in first episode patients (Friedman et al, 2008;Kong et al, 2011). This implies a progressive nature associated with illness duration in schizophrenia, as previously reported in a structural study investigating GM and WM volumes reporting a progressive reduction in the frontal WM volume in patients (Ho et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although causality still needs to be proven, there is notable evidence suggesting that impaired white matter integrity in the corpus callosum, the anterior limb of the internal capsule, and the uncinate fasciculus might be biological vulnerability factors of bipolar disorder. However, enthusiasm for this assumption has been limited by the fact that reductions of white matter integrity, especially of the corpus callosum [221][222][223][224][225][226][227][228], the anterior limb of the internal capsule, and the uncinate fasciculus, have also been reported for schizophrenia and unipolar depression [173,183,[229][230][231][232][233]. Thus, reported white matter abnormalities might not be a vulnerability specific to bipolar disorder, but they seem linked to clinical features like impulsivity, psychosis, and depressive mood as well.…”
Section: White Matter Alterations In Network Associated With Emotionmentioning
confidence: 99%